Popular writing and the Great War: A Copernican revolution - Gibelli, Antonio (REVISTA DE HISTORIOGRAFÍA (RevHisto), 2022)
Did the lower classes write their “diary” of the First World War? Until the 1970s, historians in Italy and beyond thought not. They had forgotten earlier examples such as that of the Austrian philologist Leo Spitzer, the first to collect and study the letters written by Italian prisoners of war. The 1970s witnessed a sudden upsurge of research interest in the letters, diaries and memoirs of ordinary soldiers and ordinary people. Here, I describe the protagonists, the scenarios and the characteristics of this revolution in perspectives on the shocking event that opened the twentieth century.